Thermal Structure of the Middle and Upper Atmosphere of Mars From ACS/TGO CO2 Spectroscopy. Issue 10 (19th October 2022) - Belyaev, D. A.; Fedorova, A. A.; Trokhimovskiy, A.; Alday, J.; Korablev, O. I.; Montmessin, F.; Starichenko, E. D.; Olsen, K. S.; Patrakeev, A. S.
Abstract: Temperature and density in the upper Martian atmosphere, above ∼100 km, are key diagnostic parameters to study processes of the species' escape, investigate the impact of solar activity, model the atmospheric circulation, and plan spacecraft descent or aerobraking maneuvers. In this paper, we report vertical profiling of carbon dioxide (CO2 ) density and temperature from the Atmospheric Chemistry Suite (ACS) solar occultations onboard the ExoMars Trace Gas Orbiter. A strong CO2 absorption band near 2.7 μm observed by the middle infrared spectrometric channel (ACS MIR) allows the retrieval of the atmospheric thermal structure in an unprecedentedly large altitude range, from 20 to 180 km. We present the latitudinal and seasonal climatology of the thermal structure for 1.5 Martian years (MYs), from the middle of MY 34 to the end of MY 35. The results show the variability of distinct atmospheric layers, such as a mesopause (derived from 70 to 145 km) and homopause, changing from 90 to 100 km at aphelion to 120–130 km at perihelion. Some short‐term homopause fluctuations are also observed depending on the dust activity. Plain Language Summary: We report vertical distributions of the density and temperature in the Martian atmosphere in the altitude range from 20 to 180 km. This broad interval of heights embraces regions of the troposphere (<50 km), the mesosphere (50–100 km), and the thermosphere (>100 km). Knowledge of thermal structure in the middle and upper atmosphere (above 50 km) is unique for the Martian climate modeling, studying the atmospheric escape and the impact of solar activity, as well as planning spacecraft maneuvers. Our data are based on remote measurements of the carbon dioxide (CO2 ) absorption in the atmosphere at very high altitude resolution of one kilometer. Sensing this major component, 95% of the total density, in the infrared wavelength range allows us to derive the atmospheric temperature as well. We observe the climatology of different atmospheric layers depending on latitude and seasons for 1.5 Martian years, from May 2018 to January 2021. For example, we reveal extremely high variability of the coldest layer, mesopause, from 70 km in the southern winter to 150 km in the southern summer. Key Points: Seasonal variability of the Martian atmospheric thermal structure at altitudes 20–180 km is reported from CO2 infrared spectroscopy The mesopause altitude rises from 70 to 90 km in the high‐winter latitudes to 130–150 km in the summer season for both hemispheres The homopause altitude varies from 90 km at aphelion to 130 km at perihelion in the Martian years 34 and 35, and it depends on dust activity